Combiner l'impact et l'effet social. - Michaud, Alexandre (Canadian Journal of Nonprofit & Social Economy Research / Revue canadienne de recherche sur les OSBL et l'économie sociale, 2023)
Social purpose organizations, whether from the community sector or the social economy, are faced with a growing number of funders demanding the adoption of private-sector productivity standards. These organizations must present reports analyzing their social impacts. At the same time, they are faced with an economic and social environment marked by crises. Issues such as climate change, wealth inequality, and systemic racism are becoming increasingly important in their communities. They are sensitive to these issues and want to understand and tackle them. However, the tools for analyzing systemic crises are different from impact assessment models. Given the importance of these two perspectives, the author imagines an analytical framework combining social efficiency modeling and macrosocial modeling. To do so, he mobilizes the principle of social effect recently developed by Philippe Dufort, which he implements within a logical model of social impact.